MODAL SOSIAL PENGRAJIN ROTAN (Studi Pada Usaha Kerajinan Rotan di Kecamatan Rumbai Kota Pekanbaru) - Rahmadani, Sri Dela; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Rattan handicraft is one of the home industries that is engaged in crafts that use the craftsmanship and agility of the hand of a craftsman so as to produce crafts that have value. The purpose of this study was to explain the profile of rattan craftsmen and find out the social capital of rattan craftsmen. This study uses a qualitative approach with descriptive analysis. The selection of informants in this study was carried out with a purposive sampling technique that is taking data from informants based on certain criteria. These criteria are the craftsmen who already have a business and place of business, the craftsmen have been members of the cooperative for approximately 5 years and the presence of social capital such as beliefs, norms or rules and networks in rattan craftsmen. Data collection techniques used in this study were observation, interviews and documentation. The results of this study state that social capital is trust that occurs between craftsmen and other craftsmen, norms or rules and networks established by craftsmen in terms of obtaining rattan raw materials, processing rattan raw materials and rattan handicraft marketing.  Keywords: Social Capital, Rattan Craftsmen